An early cost analysis of magnetic bone growth stimulation in England. (2nd January 2022) - Russell, Joel; Sprague, Sheila; Harper, Sam; Green, Michelle; Bhandari, Mohit
ABSTRACT: Background: Fracture nonunions impact on morbidity and health care costs and are associated with substantial pain, reduced mobility, prolonged morbidity, and a lower quality of life. CMF OrthoLogic 1000 (OL1000) is a bone growth stimulator used to promote fracture healing potentially reducing the need for surgical intervention. A cost analysis comparing CMF OL1000 versus surgical care for patients with nonunion tibial fractures was conducted. Methods: A Markov model was developed to compare the difference in costs between CMF OL1000 versus surgical care within the English National Health Service over a 2-year time horizon. The effectiveness of CMF OL1000 was based on recently published registry data. Cost data were derived from published sources and national cost databases. Sensitivity and scenario analyses were conducted. Results: The use of CMF OL1000 is estimated to lead to cost-savings of £1, 104 per patient, a reduction in average healing time of 2.1 months and a relative risk of infection of 0.19 compared to immediate surgical intervention (standard of care). The results of the model are robust to most changes in input parameters and scenarios considered. Conclusions: This early analysis shows cost-savings for CMF OL1000 compared with surgical intervention for individuals with nonunion tibial fractures.